Interdisciplinarity teaching of fashion design (ModaPalavra e-periódico, 2013)
This article discusses the importance of interdisciplinarity in the undergraduate courses in fashion design, bringing as an example of this practice joint activity in the disciplines of fashion design and computer science to fashion to achieve better results in the construction of the illustration, whether manual or digital.
Keywords: Interdisciplinarity; Illustration; Fashion